PENERAPAN PROSEDUR AUDIT ATAS AKUN PIUTANG USAHA PT FI OLEH KANTOR AKUNTAN PUBLIK MENNIX & REKAN - Fikri Ihsan Munawar Rahman (2022)
Accounts receivable in the statement of financial position is an important account after cash and cash equivalents. Because this account is also included in the category of current assets which are usually presented in the statement of financial position with a fairly material value. Accounts receivables are easy to convert into cash, because they include current assets with maturities of less than 1 year. Therefore, accounts receivables are also vulnerable to being stolen, misappropriated, and fraudulent, need for good internal control to prevent the possibility of fraud in these accounts. An audit of the account is required to be carried out by an independent person, namely the auditor. The object of this final project is one of the clients of KAP Mennix and Partners, namely PT FI. The author was given the opportunity by a senior auditor to implement the accounts receivable audit procedures at PT FI. Accounts receivable audit procedures carried out by KAP Mennix and Partners, determining materiality, conducting vouching, checking accounts receivable lists, making working papers, confirming accounts receivables, making confirmation controls, and making subsequent collections of trade receivables. There are 3 (three) audit findings on accounts receivable accounts at PT FI, the existence of negative accounts receivable, the difference in receivables per client and per confirmation, and the difference in the exchange rate of foreign currency trade receivables. Based on these results, the auditor has made adjustments to the appropriate balance.